Bakti Sosial Sunat Massal Gratis Dalam Rangka Kolaborasi Lintas Sektor Memperingati Pesta Rakyat Agustusan Untuk Kesehatan Masyarakat di Kampus Universitas Sunan Giri Surabaya - Abdullah Ilmi; Rizal Muhaimin; Alfina Rahma; Rommy Hardyansah; Bambang Aji Prasetyo; Heriyana Amir; Muas Mubarak; Adi Herisasono; Mujito Mujito (Lembaga Pengembangan Kinerja Dosen, 2024)
The free mass circumcision social service activity held at Sunan Giri University Surabaya is a cross-sector collaboration initiative to commemorate the August people's party. This activity aims to improve public health, especially among children, by providing quality and free medical services. Involving various parties, including government agencies, non-governmental organizations, and local communities, this activity not only educates the public about the importance of reproductive health, but also strengthens social solidarity. In its implementation, this activity succeeded in attracting active participation from the surrounding community, creating awareness of the importance of children's health and welfare, and fostering a spirit of mutual cooperation. The results of this activity are expected to be a model for similar initiatives in the future, as well as providing long-term positive impacts on public health in the area